2017
DOI: 10.1038/srep40550
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Mechanically Robust Poly(m-phenylene isophthalamide) Nanofiber/nets for Ultrathin High-Efficiency Air Filter

Abstract: Effective promotion of air filtration applications proposed for fibers requires their real nanoscale diameter, optimized pore structure, and high service strength; however, creating such filter medium has proved to be a tremendous challenge. This study first establishes a strategy to design and fabricate novel poly(m-phenylene isophthalamide) nanofiber/nets (PMIA NF/N) air filter via electrospinning/netting. Our strategy results in generation of a bimodal structure including a scaffold of nanofibers and abunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 46 publications
(74 reference statements)
2
75
0
Order By: Relevance
“…Previously, pieces of 2D nanonets with true nanoscale diameters (<50 nm) were found by our group, which hold great promise as an ideal candidate for air filtration due to their unique 2D network structure . However, up to now, only several special polymers of polyamide, poly( m ‐phenylene isophthalamide), and polyurethane have been processed into nanonets and used as air filters . And, these nanonets usually distributed sparsely among nanofibers and contained partly nonporous films caused by the uncontrollable phase separation of charged fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, pieces of 2D nanonets with true nanoscale diameters (<50 nm) were found by our group, which hold great promise as an ideal candidate for air filtration due to their unique 2D network structure . However, up to now, only several special polymers of polyamide, poly( m ‐phenylene isophthalamide), and polyurethane have been processed into nanonets and used as air filters . And, these nanonets usually distributed sparsely among nanofibers and contained partly nonporous films caused by the uncontrollable phase separation of charged fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Figure illustrates the FE‐SEM images of NFNM obtained under optimum conditions with novel 3D web‐like nano‐nets comprising interlinked nanowires. Previous studies showed that the nano‐net has a positive effect on mechanical properties of fibrous webs via “nets bonding” . In this research, the goal is to get optimum value of CTAB concentration for NFNM characteristic improvement.…”
Section: Resultsmentioning
confidence: 98%
“…Electrospinning/netting (ESN) is an advanced and novel electro‐hydrodynamic technique in the one‐step fabrication of “nano‐nets” with ultrathin nanowire (diameter: ∼30 nm), smaller pore size and large quantities . Researchers have reported that this unique structure could improve the membranes mechanical properties .…”
Section: Introductionmentioning
confidence: 99%
“…In our view, the nanofiber web's fracture mechanism can be divided into four phases represented by elongation/slippage, breakage of weaker part/slippage, further fracture, and maximum fracture leading to catastrophic failure of the structure. At phase one, nanofibers tend to deform under small stress: linear elongation and slow slippage of nanofibers resulting in the rapid increase in extension and linear elastic behavior . At phase two, tensile stress continually increases, and weak nanofibers show partial break‐up and continue slippage, which corresponds to the relatively slow increase of tensile strain in the stress–stain curve .…”
Section: Resultsmentioning
confidence: 99%